2019
DOI: 10.3390/cancers11081210
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Gender-Related Anticancer Research on Mitochondrial Regulator Sodium Dichloroacetate in Preclinical Studies In Vivo

Abstract: Sodium dichloroacetate (DCA) is an investigational medicinal product which has a potential anticancer preparation as a metabolic regulator in cancer cells’ mitochondria. Inhibition of pyruvate dehydrogenase kinases by DCA keeps the pyruvate dehydrogenase complex in the active form, resulting in decreased lactic acid in the tumor microenvironment. This literature review displays the preclinical research data on DCA’s effects on the cell pyruvate dehydrogenase deficiency, pyruvate mitochondrial oxidative phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 216 publications
0
19
1
Order By: Relevance
“…17,18,41 The monotherapy with NaDCA, as a mitochondrial regulator, illustrates antitumor effects in in vivo models. 24 The study of U87 and PBT24 tumors control peculiarities indicate their similar malignancy. The biomicroscopic, histomorphological analysis revealed that U87 and PBT24 tumors exhibit different sensitivity between treatment with NaDCA and MgDCA; that the efficacy of investigational medicines for xenograft growth, invasion into CAM, angiogenesis depends not only on the dichloroacetate anion concentration but also on the cation in the salt.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…17,18,41 The monotherapy with NaDCA, as a mitochondrial regulator, illustrates antitumor effects in in vivo models. 24 The study of U87 and PBT24 tumors control peculiarities indicate their similar malignancy. The biomicroscopic, histomorphological analysis revealed that U87 and PBT24 tumors exhibit different sensitivity between treatment with NaDCA and MgDCA; that the efficacy of investigational medicines for xenograft growth, invasion into CAM, angiogenesis depends not only on the dichloroacetate anion concentration but also on the cation in the salt.…”
Section: Discussionmentioning
confidence: 97%
“… 17 , 18 , 41 The monotherapy with NaDCA, as a mitochondrial regulator, illustrates antitumor effects in in vivo models. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichloroacetic acid (DCA) and its sodium or diisopropylammonium salt, pyruvate dehydrogenase kinase (PDK) inhibitors, have been well known to possess diverse pharmacologic properties, e.g., antitumor, 26 anticancer, 27 antimetabolic agents, 28 therapeutic agents, 29 oral antidiabetic agents, 30 and more. However, the phytotoxicity of DCA to weed plants has been barely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting point in gender-related anticancer treatment is the topic of the review of Stakisaitis et al: "The Importance of Gender-Related Anticancer Research on Mitochondrial regulator Sodium Dichloroacetate in Preclinical Studies In Vivo" [2]. The review describes an excellent example of such gender-related effect by cancer treatment with sodium dichloroacetate.…”
mentioning
confidence: 99%